2017
DOI: 10.5005/jp-journals-10005-1450
|View full text |Cite
|
Sign up to set email alerts
|

Eruption Chronology in Children: A Cross-sectional Study

Abstract: Aims and objectives The purpose of this study is to determine the appropriate reference standard for eruption timing of primary teeth in infants and preschool children of Bhopal city and to determine the role of various factors affecting the eruption of primary dentition.Materials and methods A cross-sectional study was conducted among the infants and preschool children (4-36 months) attending the local government or private hospitals, and vaccination centers. Prior to the study, Institutional Ethical Committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 86 publications
0
23
3
4
Order By: Relevance
“…Similarly, the mean ETFPT of Indian children was 8.15 ± 1.69 months in a major city in North India 30 and 9.50 ± 2.70 months in Singapore 24 . Meanwhile, another study in India reported that the mean ETFPT of Indian children in Bhopal was 11.40 ± 3.43 months 31 . Although differences in tooth eruption timing between shared ancestry populations in different countries/communities do exist, the reasons may include nutrition, socioeconomic status, climate, and environmental factors, such as the fluoride content in drinking water 30 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the mean ETFPT of Indian children was 8.15 ± 1.69 months in a major city in North India 30 and 9.50 ± 2.70 months in Singapore 24 . Meanwhile, another study in India reported that the mean ETFPT of Indian children in Bhopal was 11.40 ± 3.43 months 31 . Although differences in tooth eruption timing between shared ancestry populations in different countries/communities do exist, the reasons may include nutrition, socioeconomic status, climate, and environmental factors, such as the fluoride content in drinking water 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The GUSTO cohort study in Singapore 24 found that compared to Chinese children, Malay and Indian children experienced significantly delayed tooth eruption. Meanwhile, primary tooth eruption timing differs between Indian children in Singapore 24 and in India 30,31 . However, there is a lack of population data for residents in Nanjing of China.…”
Section: Introductionmentioning
confidence: 99%
“…The examination time point was planned in children who had just completed primary dentition, which normally occurs by 30 months. 19 In six subjects, upper and/or lower second deciduous molars had not yet erupted, while all others had fully formed primary dentition. The age range of those without fully erupted dentition was 32-42 months.…”
Section: Discussionmentioning
confidence: 92%
“…Eruption timing depends on the population studied. Norms are typically specific for populations (Baylis & B. R., ; Verma et al, ).…”
Section: Definitionsmentioning
confidence: 99%